Highly sensitive detection of copper(i) and copper(ii) in cell specimens by CE-UV with large-volume sample stacking. Issue 21 (19th May 2016) - Chen, Cheng; Li, Xin; Xie, Xia; Chang, Fengxia; Li, Meixian; Zhu, Zhiwei
Abstract : A CE-UV method has been developed for the simultaneous separation and sensitive determination of copper(i ) and copper(ii ) in cell specimens. Abstract : A sensitive, rapid and simple CE-UV method with large-volume sample stacking (LVSS) and polarity switching has been developed and validated for the analysis of copper(i ) and copper(ii ) simultaneously. Benefiting from the combination of the LVSS method, a limit of detection (LOD) of 30 nM was obtained which was much lower than those of the current detection methods. Several factors, such as the concentration and pH of the background solution, injection time and pressure, stacking voltage and inversion electric current, were systematically optimized. Under the optimum conditions, the detection limits of copper(i ) and copper(ii ) were improved nearly 1000 times compared with the conventional methods by CE-UV, which made it possible to determine trace copper in cell specimens. Eventually, the proposed method was successfully applied to detect copper(i ) and copper(ii ) in spiked cell samples with good recoveries.